The Change in Distance Between Bilateral Internal Carotid Arteries in Acromegaly and Its Risk Factors - Yan, Xiaorong; Chen, Xiaoyong; Ge, Hongliang; Zhu, Shinong; Lin, Yuanxiang; Kang, Dezhi; Lin, Zhangya; Jiang, Changzhen; Ding, Chenyu (Frontiers in Endocrinology, 2020)
Background: Studies investigating the change in distance between the bilateral internal carotid arteries (ICAs) in acromegalic patients have provided ambiguous results. The influencing factors of these changes have not been well identified. Objective: To further investigate the change in distance between bilateral ICAs in acromegaly patients and identify the influencing factors of the change. Method: Patients diagnosed as acromegaly from Jan 2016 to Sep 2019 in the Department of Neurosurgery of the First Affiliated Hospital of Fujian Medical University, were included in this study. Computed tomography angiography (CTA) or magnetic resonance angiography (MRA) data were obtained for all patients for three-dimensional reconstruction of the ICAs. Distance between bilateral ICAs was measured and recorded for assessment. Result: 172 patients including 86 cases with acromegaly in the study group and 86 cases with non-functional pituitary adenoma in the control group were enrolled in this study. The difference of adenoma sizes between two groups was not statistically significant. Patients in acromegaly group had significantly larger maximum distances between bilateral siphon carotid ectasias (25.5±4.1 mm vs. 23.4±3.5 mm, P=0.001) and between bilateral lacerum segments (26.2±3.2 mm vs. 24.1±4.3 mm, P<0.001) compared with those of patients with non-functional pituitary adenomas. Multivariate analysis showed that the increased bilateral ICAs distance was associated with disease duration (odds ratio = 1.01, 95% confidence interval = 1.01-1.02, P=0.005) and refractory pituitary adenoma (odds ratio=9.8, 95% confidence interval=1.1-88.7, P=0.043) but not with level of grow hormone (GH), insulin-like growth factor-1 (IGF-1) and adenoma size in acromegaly. Conclusion: Our study showed significant change in distance between the bilateral ICAs in acromegalic patients, comparing to patients with non-functional pituitary adenomas. The increased intercarotid artery distance is associated with disease duration but not with preoperative level of GH and IGF-1. Refractory pituitary adenoma and longer disease duration are the both risk factors of the increased ICAs distance in patient with acromegly.